Interaksi Komunikasi Keluarga dalam Era Generasi Digital: Implikasi pada Orang Tua dan Remaja di Desa Gajing Jaya - Ariana Balqis; Manap Solihat (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2026)
The rise of digital technology has greatly reshaped family communication patterns, especially between parents and adolescents in Gajing Jaya Village. This qualitative research aims to explore how these changes affect the emotional and social connections among family members. The findingsindicate that, despite the growing reliance on digital media for interaction, face to face communication remains esential to maintain closeness and mutual understanding. Parents and adolescents respond to technology in different ways; parents strive to set supportive rules that maintain emotional bonds, whille adolescents leverage technology to broaen their social circles. The study emphasizes that maintaining harmonious family communication in the digital age depends largely on balencing technology use as a tool to strengthen relationships. The continuous adaption of paretal roles and adolescents awareness of digital communication ethics are crucial for sustaining harmony amid ongoing changes.